The impact of short hospital stay on prognosis after acute myocardial infarction: An analysis from the ACSIS database. Issue 6 (26th May 2021) - Tomer, Orr; Leibowitz, David; Einhorn‐Cohen, Michal; Shlomo, Nir; Dobrecky‐Mery, Idit; Blatt, Alex; Meisel, Simcha; Alcalai, Ronny
Abstract: Background: Current evidence regarding the optimal length of hospital stay (LOS) following myocardial infarction (MI) is limited. This study aimed to examine LOS policy for MI patients and to assess the safety of early discharge. Methods: A prospective observational study that included patients with STEMI and NSTEMI enrolled in the Acute Coronary Syndrome Israeli Survey (ACSIS) during the years 2000–2016. Patients were divided into three subgroups according to their LOS: <3 days (short‐LOS), 3–6 days (intermediate‐LOS) and >6 days (long‐LOS). We compared baseline characteristics, management strategies and clinical outcomes at 30 days and 1 year in these groups. Results: Ten thousand four hundred and fifty eight patients were enrolled in the study. The LOS of MI patients gradually decreased over time. Short‐LOS and intermediate‐LOS patients had similar clinical characteristics while patients in the long‐LOS group were older with more co‐morbidity. There was no difference in the clinical outcomes, including re‐MI, arrhythmias, 30 days MACE, and 30 days mortality between the short‐LOS and intermediate‐LOS groups. However, the rate of re‐hospitalizations was higher in the short‐LOS group (20.9% vs. 17.8%, p  = .004) without evidence of increased cardiovascular events. In multivariate analysis, the LOS did not predict either 30 days mortality (HR: 1.3; CI:0.45–5.48), nor MACE at 30 days (HR: 1.1; CI:0.79–1.56). Conclusion: Our study suggests that an early discharge strategy of up to 3 days from admission is safe for low and intermediate‐risk patients after both STEMI and NSTEMI. Nevertheless, this strategy is associated with an increased risk of potential avoidable readmission and there might be psychological and social factors that may warrant a longer stay.